Settlement in tax evasion prosecution - Macho-Stadler, Inés,Pérez-Castrillo, J. David (Univ., Center for Economic Studies [u.a.], 2002)
It is often argued that even if optimal ex-post, settlement dilutes deterrence ex-ante. We analyze the interest for the tax authority of committing, ex-ante, to a settlement strategy. We show that to commit to the use of settlements is ex-ante optimal when the tax authority receives signals that provide statistical information about the taxpayers' true tax liability. The more informative the signal, the larger the additional expected revenue raised by the tax authority when using settlement as a policy tool.
Internetausg.: http://www.cesifo.de/pls/ifo_app/DocLinkCESifoDl?getDoc=cesifo_wp814.pdf
Keywords: Arbeitspapier; Graue Literatur; Steuerstrafrecht; Steuerfahndung; Verhandlungstheorie; Unvollkommene Information; Theorie; Rechtsdurchsetzung